What matters to women during childbirth: A systematic qualitative review - Downe, Soo; Finlayson, Kenneth; Oladapo, Olufemi; Bonet, Mercedes; Gülmezoglu, A. Metin (PLOS ONE, 2018)
Introduction Design and provision of good quality maternity care should incorporate what matters to childbearing women. This qualitative systematic review was undertaken to inform WHO intrapartum guidelines. Methods Using a pre-determined search strategy, we searched Medline, CINAHL, PsycINFO, AMED, EMBASE, LILACS, AJOL, and reference lists of eligible studies published 1996-August 2016 (updated to January 2018), reporting qualitative data on womens’ childbirth beliefs, expectations, and values. Studies including specific interventions or health conditions were excluded. PRISMA guidelines were followed. Data collection and analysis Authors’ findings were extracted, logged on a study-specific data form, and synthesised using meta-ethnographic techniques. Confidence in the quality, coherence, relevance and adequacy of data underpinning the resulting themes was assessed using GRADE-CERQual. A line of argument synthesis was developed. Results 35 studies (19 countries) were included in the primary search, and 2 in the update. Confidence in most results was moderate to high. What mattered to most women was a positive experience that fulfilled or exceeded their prior personal and socio-cultural beliefs and expectations. This included giving birth to a healthy baby in a clinically and psychologically safe environment with practical and emotional support from birth companions, and competent, reassuring, kind clinical staff. Most wanted a physiological labour and birth, while acknowledging that birth can be unpredictable and frightening, and that they may need to ‘go with the flow’. If intervention was needed or wanted, women wanted to retain a sense of personal achievement and control through active decision-making. These values and expectations were mediated through womens’ embodied (physical and psychosocial) experience of pregnancy and birth; local familial and sociocultural norms; and encounters with local maternity services and staff. Conclusions Most healthy childbearing women want a positive birth experience. Safety and psychosocial wellbeing are equally valued. Maternity care should be designed to fulfil or exceed womens’ personal and socio-cultural beliefs and expectations.